2009
DOI: 10.1007/s10570-009-9313-1
|View full text |Cite
|
Sign up to set email alerts
|

Can delignification decrease cellulose digestibility in acid pretreated corn stover?

Abstract: It has previously been shown that the improved digestibility of dilute acid pretreated corn stover is at least partially due to the removal of xylan and the consequent increase in accessibility of the cellulose to cellobiohydrolase enzymes. We now report on the impact that lignin removal has on the accessibility and digestibility of dilute acid pretreated corn stover. Samples of corn stover were subjected to dilute sulfuric acid pretreatment with and without simultaneous (partial) lignin removal. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 29 publications
10
79
0
1
Order By: Relevance
“…However, the hemicellulose removal cannot by itself explain the coalescence, since there seems to be no fibril coalescence under low-temperature alkaline conditions that also remove hemicelluloses (Fahlén and Salmén 2003). The additional removal of lignin combined with the hemicellulose removal seems to give the microfibrils even more possibility to coalesce (Ishizawa et al 2009). The coalescence during chemical pulping may also be due to the softening of the lignin network (Fahlén and Salmén 2003).…”
Section: Cell Wall Compositionmentioning
confidence: 99%
“…However, the hemicellulose removal cannot by itself explain the coalescence, since there seems to be no fibril coalescence under low-temperature alkaline conditions that also remove hemicelluloses (Fahlén and Salmén 2003). The additional removal of lignin combined with the hemicellulose removal seems to give the microfibrils even more possibility to coalesce (Ishizawa et al 2009). The coalescence during chemical pulping may also be due to the softening of the lignin network (Fahlén and Salmén 2003).…”
Section: Cell Wall Compositionmentioning
confidence: 99%
“…Reductions in cellulose accessibility resulting from cellulose aggregation induced by sufficient removal of noncellulosic components in the cell wall would explain both reduced hydrolysis kinetics, as well as limited cellulose hydrolysis. 30 The cellulase enzyme cocktail used in this study (i.e., CTec3) has been shown to contain a suite of accessory enzymes including xylanase and pectinase activities. 31 Furthermore, this cocktail is capable of effectively hydrolyzing pretreated biomass with low to moderate hemicellulose content without any additional accessory enzymes; 31 however, significantly lower yields are observed in pretreated feedstocks containing a substantial fraction of the original xylan, such as the AHP-only samples.…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
“…Lignin also tends to irreversibly bind the enzymes through hydrophobic interactions causing a loss in cellulases activities 14,15,16 .In addition, during the pretreatment step lignin suffer changes in its structure and the effects on the enzymatic hydrolysis of cellulose are not completely understood 17,18 . For instance, the chemical removal of lignin after dilute acid pretreatment reduced the cellulose conversion possibly due to the aggregation of cellulose microfibrills in bundles that hindered the enzymes penetration 6,19 . On the other hand, Zhu et al 20 removed xylans from hardwood species improving the enzymatic digestibility of the substrate due to dissolution of acetyl and uronic acid groups, while the lignin removal was not the most important factor for enhancing cellulose hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Autohydrolysis pretreatment fails to remove high amounts of lignin, but the structure and distribution of this macromolecule over and inside the cell walls is altered, and has been demonstrated that, in some cases, it can affect the enzymatic access to the cellulose 25 . Some authors have reported that after hydrothermal and diluted acid pretreatments, the glucose yields from enzymatic hydrolysis was higher even when the lignin removal was minimal 19,26 . Many researchers have indicated that the combination of processes such as autohydrolysis and alkaline washing could increase the accessibility of cellulose to the enzymatic hydrolysis by removing recalcitrant lignin, improving the cellulose digestibility 24,27,28 .…”
Section: Introductionmentioning
confidence: 99%